<span>f(x)=5x+3/6x+7
This means that f(6/x) = [</span>5(6/x)+3] / [6(6/x)+7] = [ 30/x +3 ] / [36/x +7]
If we assume x≠0 , f(6/x) = [30 +3x]/ [36 + 7x]
g(x)=√<span> [ x^2-4x ]
</span>
g(x-4) = √ [ (x-4)^2-4(x-4) ] = √ [ x² -8x +16 -4x +16 ] = √ [ x^2-12x +32]
Answer:
3
Step-by-step explanation:
Answer:
a= 4.993
c = 5.824
A= 59°
C = 90°
Step-by-step explanation:
b=3, B=31°
Since it's a right angle.
C = 90°
A = 180-90-31
A= 59°
For side a and c
a/sin A = b /sin B
a = sinA * b/sin B
a= sin 59 * 3/sin31
a= 4.993
a = 5
c/sin C = b/sin B
c = sin C * b/sin B
c = sin90 * 3/sin 31
c = 1* 5.824
c = 5.824
Answer: X does not intercept (none)
Y=(0,5)
Step-by-step explanation: